The coomunity structure of mangroves at Nabitasan, Leganes, Iloilo. - Sanguillosa, Jerry B. (2011.)
Mangrove forests are unique intertidal ecosystems that are found on relatively sheltered coastlines, deltas, estuaries, and lagoons in tropical and subtropical regions of the world. this study was conducted to assess the community structure of reforested mangroves at Nabitasan, leganes, Iloilo, using the transect line plot method. Specifically, it aims to detemine selected physico-chemical parameters such as the salinity, pH an temperature of soil and water and the characterization of substrate; identify and classify true mangrove species present in the area; and describe the community structure in terms of stand basal area, stems per hectare, relative density, relative frequency, importance value, Shannon index of diversity, zonation patterns, seedling and sapling density. No previous study was done in documenting the community structure of mangrove in Nabitasan, Leganes, Iloilo thus, sthis study is important in providing vital information needed for its proper management and preservation. Twelve plots were established in one station. One true mangrove was identified belonging to one family. Avivenniaceae-Avicennia marina. The study area had a water salinity range of 34 ppt to 35ppt; soil salinity range of 20ppt to 29 ppt; water temperature range of 32 degrees centigrade to 36 degrees centigrade; soil temperature range of 29 degrees centigrade to 33 degrees centigrade; water pH range 7.58 to 7.74; and soil pH 7.57 to 7.89. Basal area ranges from 9.5 m squared / ha t0 2.13 m squared/ ha. The average stand basal area was 4.54 m squared / ha for th study area. The total average of stems per hectare for the study area was 5541. The study area had the same value of 100 for relative density, frequency and dominance for Avicennia marina species. The importance value was 300 for the Avicennia marina. The study area had zero Index Diversity or no diversity. Seedling of Avicennia marina had a total of 5449 for the study area. Saplings of Avicennia marina had a total of 285 for the study area. The substrate was muddy, sandy to corraline. Reforestation of other mangrove species is needed and demaarcation of the present mangrove area is recommended.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Magroves -- Nabitasan, Leganes, Iloilo